The role of smallholder bean farmers in determining farm gate prices for beans in Uganda - Jjagwe, G.; Kibwika, P.; Mazur, R.; Sseguya, H. (Springer, 2022)
Like for other agricultural commodities, the bean value chain involves a series of actors including; farmers as producers, middlemen, retailers, wholesalers and exporters. The study explains the common bean (Phaseolus vulgaris) marketing constraints faced by smallholder bean farmers and other actors in the bean value market chain that need redress for efficient and effective bean marketing in Uganda. Specifically, the effect of farmer bean production and marketing modes, and limited knowledge about bean market requirements on the final prices received for their beans and their limited ability to demand better prices is explained by the study. A descriptive cross-sectional design was used to collect data from 127 farmers (in strata of trained and non-trained farmers), 34 traders, five input dealers and 40 consumers, using semi structured questionnaires, and interview guides. Quantitative and qualitative data were analysed using SPSS and content analysis, respectively.